2018
DOI: 10.1111/jac.12302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperature on pollen morphology, plant growth and seed yield in quinoa (Chenopodium quinoa Willd.)

Abstract: Quinoa (Chenopodium quinoa Willd.) has gained considerable attention worldwide during the past decade due to its nutritional and health benefits. However, its susceptibility to high temperatures has been reported as a serious obstacle to its global production. The objective of this study was to evaluate quinoa growth and pollen morphology in response to high temperatures. Pollen morphology and viability, plant growth and seed set, and several physiological parameters were measured at anthesis in two genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 89 publications
(185 reference statements)
5
106
1
1
Order By: Relevance
“…35–40 days old). Previous studies in both growth chambers and in the field showed that temperatures above 32°C impaired the yield and caused physiological and phenotypic changes in quinoa (Bazile et al , ; Hinojosa, Matanguihan, et al , ), and therefore the growth chamber temperature was set to 35°C. We found that the soil temperature was 30°C when the air temperature was 35°C, and therefore 30°C was selected as the heat treatment for roots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35–40 days old). Previous studies in both growth chambers and in the field showed that temperatures above 32°C impaired the yield and caused physiological and phenotypic changes in quinoa (Bazile et al , ; Hinojosa, Matanguihan, et al , ), and therefore the growth chamber temperature was set to 35°C. We found that the soil temperature was 30°C when the air temperature was 35°C, and therefore 30°C was selected as the heat treatment for roots.…”
Section: Resultsmentioning
confidence: 99%
“…There is growing interest in expanding quinoa cultivation (Jacobsen, ; Pulvento et al , ; Choukr‐Allah et al , ; Bazile et al , ; Maliro et al , ), because of its nutritious grain (Repo‐Carrasco et al , ; Vega‐Gálvez et al , ; Choukr‐Allah et al , ) and its ability to grow on poor soils (Jacobsen et al , ). Heat is a major limitation to expanding quinoa cultivation (Lesjak and Calderini, ; Hinojosa, Matanguihan, et al , ), however, and quinoa generally does poorly in climates with average temperatures higher than 32°C (Bazile et al , ; Hinojosa, Matanguihan, et al , ). A goal of this study is to gain a better understanding of how heat limits grain production in quinoa.…”
Section: Introductionmentioning
confidence: 99%
“…In Pison, QQ74 and 17GR, stomatal conductance was not affected by heat stress. Opened stomata at high temperature (40/24°C day/night) in QQ74 and 17GR cool the leaves through transpiration (Hinojosa et al ., ). High temperature caused stomatal opening in quinoa cultivars ‘Titicaca’ and ‘Achachino’, and in other species such as Lens culinaris , Hordeum vulgare , Nicotiana tabacum and A. thaliana (Rizhsky et al ., , ; Yang et al ., ; Becker et al ., ; Cantalapiedra et al ., ; Sehgal et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Although quinoa is adapted to marginal environments, its yield can be diminished by high temperature (Bhargava et al ., ; Pulvento et al ., ; Hirich et al ., ; Peterson and Murphy, ; Bazile et al ., ; Eisa et al ., ; Lesjak and Calderini, ; Hinojosa et al ., ) or drought (Walters et al ., ; Al‐Naggar et al ., ). However, warm temperatures (28/20°C) were shown to increase plant height, photosynthesis rate, stomatal size and seed yield in quinoa (Yang et al ., ; Becker et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation